Empowering Physics Learning Plan Subjects with IFTAR Digital Module: A Study of Validity and Practicality - Ziola Natasya; Festiyed Festiyed; Desnita Desnita (Postgraduate, University of Mataram, 2025)
Sociaty 5.0 era has placed artificial intelligence (AI) and the internet of things (IoT) as fundamental aspects of human activity. The Indonesian government has paid great attention to the digitisation of learning through a curriculum that focused to use of technology, project-based learning, and the strengthening of digital competencies relevant to the needs of industry and society. However, facts in the field show that the learning tools developed by students as prospective teachers still don’t make optimal use of technology. The purpose of this study is to produce digital modules that are valid in terms of material, media, and construct and are practical for use in physics-based learning. Implications. This study used Plomp's research design, which consists preliminary research, prototyping phase, and assessment phase. The prototyping phase included Kemp's learning model design, product design, and product quality testing in the form of validity and practicality. The findings state that the validity according to experts is 0.90 (very high), the practicality according to lecturers is 0.93 (very high), and according to students is 0.92 (very high). This study is expected to improve students' pedagogical competence, encourage the optimal use of ICT, develop digital teaching material development skills, and strengthen academic character